Functional Model of RFID-Based Students Attendance Management System In Higher Education Institution - Koko Wahyu Prasetyo; Setiabudi Sakaria (IC-ITECHS, 2014)
The need of developing student attendance management system is driven due to the fact that the students’ attendance records are one of the most important factors of their academic achievement. The conventional practice of managing the student attendance manually by pens and papers is considered as challenging tasks for most of the higher education institutions. This paper will propose a system functional model to manage the student attendance in a more efficient way by utilizing the RFID tags technology. The RFID technology is an automated identification and data collection technology. The ability of RFID tags to deliver accurate information in quicker way shall improve the efficiency to manage the students attendance data. The system model proposed in this paper will also consider the need of the academic administrative staff to have an integrated reporting function which are related to the student and the lecturer attendance records. The system functional models presented in this paper are developed in UML based on the approach of object-oriented system analysis and design.